Urban Farming In The City Center: Transforming Yard Spaces Into Sources Of Food And Family Income - R. Nia Marotina (Faculty of Economics and Islamic Business State Islamic University of Palangka Raya, 2025)
Rapid urbanization in urban areas has led to the conversion of agricultural land into residential areas and infrastructure, which has had a direct impact on the decline in local food availability and increased dependence on supplies from outside the city. Urban farming or city farming has emerged as an innovative and sustainable solution to strengthen food security, especially for low-income communities. This community service activity was carried out in the Kuripan Yosorejo sub-district using a Participatory Action Research (PAR) approach, which involved 30 active participants in training and assistance in cultivating food crops in their yards. The crops cultivated include fast-growing vegetables such as spinach, kale, pak choi, and sweet corn. The results of the activity show that more than 80% of the plants grew well, and around 60% of participants used the harvest for family consumption, while the other 20% sold their produce on a small scale. In addition to economic and nutritional benefits, this program also has social and environmental impacts, such as increased interaction between residents, greening of the home environment, and increased awareness of the importance of healthy food consumption. Urban farming has proven to not only provide solutions to food issues but also strengthen the role of households as producers and agents of change in urban areas. Moving forward, this activity has the potential to be expanded through multi-stakeholder collaboration to create resilient, healthy, and empowered cities.